Budgeting : profit planning and control - Welsch, Glenn A.; Hilton, Ronald W.; Gordon, Paul N. (New Delhi : Prentice-Hall, 1992)
In this edition, all of the topics covered in the fourth edition have been retained in the book, but also expands coverage in key areas. A thorough comprehensive approach to the topic of budgeting and covers all aspect budgeting process from details of preparing many schedules that comprise a master budget to the fundamental managerial issues that are affected by the profit planning control process.
Includes bibliographical references and index.
ne 05/03/2020
Loans
Keywords: Budget in business; Budgeting